KEKERASAN SEKSUAL TERHADAP PEREMPUAN PERSPEKTIF FIKIH KLASIK - Suwarjin Suwarjin (Universitas Islam Negeri Fatmawati Sukarno, 2017)
Books circulating widely in Indonesia and viewed as authoritative regarding sexual issues generally place women as subordinate men. Men are leaders and rulers of women, while women as guided must obey the husband’s command. The piety of a wife is measured by how far the devotion of her body soul to her husband. The virtuous wife is the one who never demands his rights from the husband, does not go out and give charity without the husband’s per- mission, does not raise his eyes and voice in the presence of the husband, does not require knowledge except with the permission of the husband, and does not worship the sunna without the blessing of the husband. If the husband does not grant his rights, then he must give up with sincerity to be saved from the terrible threat of God’s punishment. Related to intimate relationships, women are positioned as sex objects, not subjects. He should not delay the sexual desire of the husband, let alone reject it. Such positions have an adverse effect on the wife. Wives often experience sexual violence and neglected their sexual rights. The underlying perspective of husband-wife sexual relationships in the jurispruden- tial books circulating in Indonesia is generally still classic and emphasizes only the power of men against women in the family. Such perspectives are no longer appropriate to the present condition, in which sexual problems are seen as a common right that should be practiced fairly between husband and wife. Allegedly there has been a distortion of understanding of husband-wife sexual relationships that need to be straightened out, in order to avoid the impression, Islam legalize sexual violence in women